Threonine phosphorylation of STAT1 safeguards gut epithelial integrity and restricts interferon-mediated cytotoxicity - Hozaifa Metwally; Maha M. Elbrashy; Hisako Kayama; Kazuki Okuyama; Ichiro Taniuchi; Kiyoshi Takeda; Tadamitsu Kishimoto (Proceedings of the National Academy of Sciences, 2025)
Barrier tissues such as the intestine are constantly challenged by environmental stressors and must adapt to maintain integrity and prevent excessive inflammation. Although traditionally viewed as a proinflammatory effector of interferon (IFN) signaling, STAT1 is shown here to play a protective role in intestinal epithelial cells (IEC) by promoting resilience to damage and restraining IFN-induced cytotoxicity. We identify phosphorylation of threonine 748 (Thr748) on STAT1 as an evolutionarily selected adaptation—highly conserved between humans and mice—that reciprocally regulates IEC integrity and IFN responsiveness. Mice expressing a phospho-deficient T748A Stat1 mutant exhibit severe colitis-induced tissue damage comparable to Stat1-deficient littermates, underscoring the critical role of Thr748 phosphorylation in mediating Stat1-driven protection during intestinal inflammation. Bone marrow transfer experiments further demonstrate that this protective effect is nonhematopoietic. Integrated genomic and transcriptomic analyses reveal that Thr748 phosphorylation modulates STAT1 DNA binding, directly activates the Itgb4 promoter, and enhances integrin β4 expression in IEC following inflammation. In intestinal organoid models, gain- and loss-of-function experiments demonstrate that Thr748 phosphorylation drives integrin β4 expression and epithelial resilience independently of IFN-induced Tyrosine 701 (Tyr701) phosphorylation. In contrast, IFN stimulation via Tyr701 induces Zbp1—a cytotoxic nucleic acid sensor—while repressing integrin β4, resulting in epithelial injury that is mitigated by Thr748 phosphorylation. Together, these findings reveal a modular architecture of STAT1 signaling in which Thr748 phosphorylation functions as a molecular rheostat that safeguards epithelial integrity while tempering IFN-driven cytotoxic responses.